2008
DOI: 10.1177/1555412008325482
|View full text |Cite
|
Sign up to set email alerts
|

Technologies Between Games and Culture

Abstract: This article introduces and situates the ensuing collection of four essays on the theme of games and technology. It argues the need for videogame studies to develop a more rigorous and focused perspective on the theorization of technology as it relates to research into games and culture. The ``and'' in games and culture cannot begin to be understood comprehensively without a thinking of the profound reliance of both terms on technology. Players and their cultural and collective involvements should be taken not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 4 publications
0
12
0
2
Order By: Relevance
“…Writing a decade ago in this journal, Crogan and Kennedy (2009) suggest game scholars take seriously the technologies “between” games and culture. In doing this, they enjoin scholars to address the various experiential changes emerging from the evolution of games as contemporary technics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Writing a decade ago in this journal, Crogan and Kennedy (2009) suggest game scholars take seriously the technologies “between” games and culture. In doing this, they enjoin scholars to address the various experiential changes emerging from the evolution of games as contemporary technics.…”
Section: Resultsmentioning
confidence: 99%
“…As Consalvo illustrates in her work, the technologies between and beyond videogames themselves significantly shape how we negotiate, understand, and value videogames and the practice of play. Extending and updating this perspective, I argue that quantified play and self-tracking are a rich and contemporary site for thinking about how assemblages of bodies and videogame technologies orient human experience and activity-a point that scholars like Crogan and Kennedy (2009), writing in this journal, draw attention to in interrogating the technologies 'between' games and culture.…”
Section: ) I Ask "What Kinds Of Practices Does Self-tracking Producementioning
confidence: 93%
See 1 more Smart Citation
“…Drawing on the cyborg, research has also shown interconnections between real life and game life (e.g. Taylor, 2006) and technology and culture (Crogan and Kennedy, 2009). Research has paid attention to how gaming allows a heightened experience of the cyborg body, through for example rumble packs and gameplay visuals (e.g.…”
Section: The Posthuman Gamermentioning
confidence: 99%
“…La pratique d'un monde ludique en ligne n'induit cependant pas seulement pour les joueurs une socialisation à un monde de représentations et de signiications, à des modes d'interaction et de coopération culturellement spéciiques. Notre approche s'inscrit, sur le thème proposé de la socialisation, dans la ligne des travaux récents qui appellent à explorer la richesse de la prise en compte simultanée des dimensions sociales, culturelles et techniques du jeu (Crogan et Kennedy, 2008). T. L. Taylor nous appelle dans ce sens à considérer les jeux comme des ensembles complexes et non déterminés de relations entre humains et non humains, empruntant pour l'analyse la notion d'assemblage à l'approche sociotechnique développée par Bruno Latour (1992).…”
Section: Du Partage Des Connaissances à La Mutualisation Des Savoirsunclassified